Implementation of the CIPP Evaluation Model of Safe School Snack Food Program (PJAS) to Create a Healthy Culture at The Junior High School Level - Wahyu Rahmawati (International Journal of Education, Language, and Religion, 2025)
The program of Pangan Jajanan Anak Sekolah (PJAS) is a government initiative to ensure the safety and quality of snacks in schools, in line with Health Law No. 17 of 2023. This study aims to evaluate the program's implementation at SMP Negeri 1 Gedangan using the Context, Input, Process, Product (CIPP) model. The study employed a descriptive qualitative approach, applied through interviews, observations, and documentation with key informants: the principal, teachers, students, parents, and the cafeteria manager. The results indicate significant achievements, such as national awards, in the implementation of Safe PJAS. Efforts include establishing an implementation team, educating vendors, collaborating with the Health Office, the Food and Drug Monitoring Agency, Community Health Centers, and the Indonesian Ulema Council, and encouraging school residents to bring their own food and drink containers. However, outreach to parents and vendors outside the school is still limited, resulting in uncontrolled consumption of food and snacks outside the school environment. Regular evaluation is needed to ensure the program's sustainability. Active parental participation and broader collaboration with relevant institutions are key to its success. This study provides policy recommendations to support the national movement for safe school snacks and encourage the growth of a healthy, productive, and well-behaved generation.